Diabatic heating governs the seasonality of the Atlantic Niño - Hyacinth C. Nnamchi (Nature Portfolio, 2021)
The relative roles of the ocean and atmosphere for the Atlantic Niño is poorly understood. Here, we show that its seasonality is governed by atmospheric diabatic heating that is associated with the seasonal migration of the inter-tropical convergence zone.